PENTINGNYA GAYA MENGAJAR GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP N 2 PAYAKUMBUH - Putri Welly; Hidayani Syam; Sandra Tifani (CV. ADIBA AISHA AMIRA, 2024)
The teaching style of educators plays a crucial role in inspiring students' motivation to learn. In the current educational context, employing the appropriate approach in the teaching process significantly impacts students' engagement levels and interest in the subject matter. This article discusses the importance of teachers' teaching styles in motivating students to learn effectively. Diverse approaches in teaching provide space for better learning differentiation, enabling teachers to understand each student's individual learning preferences. By utilizing innovative methods such as integrating technology in teaching, collaborative approaches, or implementing curricula relevant to daily life, teachers can create a learning environment that sparks students' interest. Moreover, motivating teaching styles focus on strengthening the relationship between teachers and students. When teachers demonstrate dedication, attention, and support for students' learning processes, it not only enhances students' self-confidence but also builds a positive relationship between teachers and students. This article highlights the importance of teachers' role as learning facilitators who inspire, encourage, and support students' holistic development. In pursuit of academic goals, it is crucial not only to deliver information but also to understand how students react to learning and how to motivate them to delve deeper into the subject matter. In conclusion, this article emphasizes that teachers' teaching styles are not merely techniques but rather skills that require sensitivity to individual students' needs. When teachers can adjust their teaching styles to match students' characteristics and requirements, they can lay a strong foundation for enhancing students' motivation to learn.